A Thematic Analysis of Chemistry Teachers’ Readiness to Implement Authentic Assessment Integrating the 4C Skills - Ella Izzatin Nada; Wiwik Kartika Sari; Nida Alkhawa; Putri Nadlifa Tiara Nita (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang, 2025)
Teachers play a crucial role in the successful implementation of authentic assessment, particularly within the context of the Merdeka Curriculum, which emphasizes the integration of 21st-century skills, or the 4Cs. This study aims to analyze the readiness of high school chemistry teachers (SMA/MA) in Semarang City to implement authentic assessment integrated with 4C skills, as well as to identify its supporting and inhibiting factors. A qualitative descriptive approach was employed, using thematic analysis supported by triangulation techniques, which included interviews, observations, and document analysis. The participants were selected through purposive sampling of 20 teachers from different schools. Data analysis was conducted through several stages: data transcription, coding, thematic categorization, and drawing conclusions. The findings reveal that chemistry teachers demonstrated a high level of readiness across four aspects: (1) Cognitive: 74% of the assessment tools were complete, indicating a good understanding of authentic assessment; (2) Physical: All respondents were in good health and had strong physical endurance; (3) Psychological: The teachers were motivated and showed strong interest in implementing authentic assessment; (4) Facilities and Infrastructure: On average, the schools had adequate facilities and resources available. Supporting factors included training, infrastructure availability, teacher collaboration, and a solid understanding of assessment concepts. The main obstacles were the lack of advanced training, significant differences in student abilities, limited time, and low technological proficiency among some teachers. These findings are expected to serve as a foundation for strengthening policy and providing continuous professional development to improve the quality of authentic assessments integrated with 4C skills